Sinergi Kebijakan Ekonomi dan Lingkungan: Menuju Pembangunan Berkelanjutan Synergy of Economic and Environmental Policies: Towards Sustainable Development: Synergy of Economic and Environmental Policies: Towards Sustainable Development - Pratama, Muhammad Anzarach; Taufiqurokhman, Taufiqurokhman; Yusuf, Muhamad (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
This study aims to analyze the synergy between economic policies and environmental policies in the context of sustainable development. The research method applied in this study is a systematic literature review, utilizing 500 scientific articles sourced from the Scopus database. Article reviews were conducted using the Vosviewer application to map and analyze the relationships between concepts as well as the main findings in the existing literature. The research findings reveal that the integration of economic and environmental policies through instruments such as carbon taxes, renewable energy subsidies, and environmental regulations that support innovation has enhanced the effectiveness in achieving sustainable development goals. Additionally, cross-sector collaboration and active stakeholder participation have proven to be key factors in creating harmonious and sustainable policies. This study contributes to the development of a research roadmap on the synergy between economic and environmental policies, providing a foundation for more in-depth and applicable future research. The limitation of this study is that the articles used are solely sourced from the Scopus database, thereby the research findings cannot comprehensively depict issues related to economic and environmental policies in various global contexts. Future research should utilize scientific articles sourced from other reputable international databases, such as Web of Science and Dimensions Scholars, to obtain a broader and deeper understanding of the synergy between economic and environmental policies. Thus, this study provides important insights for policymakers in designing effective strategies to achieve sustainable development through the integration of economic and environmental policies.